DEVELOPMENT OF ORTHOGONAL TIME FREQUENCY SPACE (OTFS) TRANSMITTER SYSTEM USING SOFTWARE DEFINED RADIO (SDR) - Wayan Githa Wiryabawa, I
The fourth generation wireless communication system or 4G (4th Generation) is currently being implemented in most countries in various parts of the world. Some countries have slowly shifted towards 5G (5th Generation) communication technology because this technology offers faster data transfer rates than previous generation technologies. The modulation system used in 4G and 5G technology today is Orthogonal Frequency Division Multiplexing (OFDM) which can be said to be quite effective for many use cases. But on the other hand, this modulation technique is quite vulnerable to signal degradation in high mobility scenarios. Therefore, 6G (6th Generation) Technology will be developed with these types of use cases in mind. One of the interesting candidates for use in 6G technology is Orthogonal Time Frequency Space (OTFS) which gives rise to a two-dimensional modulation format that is resistant to the Doppler effect due to high mobility. In this final project, a research was conducted to make a transmitter prototype of the OTFS modulation system that can transmit signals wirelessly at a frequency of 3.5 GHz. The prototype design process utilizes MATLAB software for baseband signal processing which is then implemented on ADALM-PLUTO Software Defined Radio (SDR) hardware. Testing is done by simulating and transmitting in real terms on a wireless channel. The test results of the OTFS system are then compared with the OFDM system. From the test results, it was found that sending images at a frequency of 3.5 GHz with a Tx gain of 0 dB and an Rx gain of 50 dB obtained a Bit Error Rate (BER) of 0.005.